The Effectiveness of Submersible Attractor Lights (SAL) in Enhancing the Economic Productivity of Gillnet Fishermen in the Madura Strait (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2025)
This study investigates the effectiveness of Submersible Attractor Lights (SAL) in improving the economic productivity of gillnet fisheries in the Madura Strait. Using experimental methods over a two-month period, this research compares catch results with and without SAL, focusing on the quantity, weight, and diversity of fish caught. The test results (U = 365.0, p = 0.0000086) indicate a statistically significant difference between gillnet catches with and without SAL. The findings reveal that SAL increases the economic value of the catch by 84.13%, demonstrating significant improvements in both productivity and profitability. Species such as Indian Mackerel (Rastrelliger kanagurta), Bigeye Scad (Selar crumenophthalmus), and Great Barracuda (Sphyraena barracuda) exhibited notable economic contributions when SAL was employed. Additionally, SAL reduced operational inefficiencies by attracting fish closer to the nets, thereby optimizing fuel and time usage. The study also acknowledges the upfront cost of SAL and operational expenses, which are outweighed by the substantial economic benefits. This research emphasizes SAL as a sustainable technological innovation with potential applications in small-scale fisheries to enhance both economic and environmental outcomes.